(untitled) (Studia Archaeologica, 2024)
The article tells about the study history of the medieval Talgar settlement and settlements in the locality. If we pay attention to the sources the first researchers and travelers of the city of Talkhiz report that the territory of the city was large. We are also talking about settlements that are part of the territory of this settlement, but have not yet been explored. Nevertheless, the Talgar settlement, which has been studied for more than one hundred and fifty years, undoubtedly has a special significance as a historical monument. Until now, valuable objects found during excavations are stored in many museums and museums-reserves of the country. Among the finds you can see some imported products. This suggests that the medieval settlement of Talgar was a center of artisans and jewelers, where international trade was well developed. One can see how much influence external relations had on the development of this settlement located along the Great Silk Road.Talgar is one of the most important monuments among the historical and cultural sites of Semirechye. However, the article says that some localities still need to be investigated. Талгарын археологийн дурсгалууд Товчлол. Уг нийтлэлд Талгарын дундад зууны үеийн суурин болон тус нутгийн сууринг судалсан түүхийн тухай өгүүлнэ. Судалгаа, тоо баримтад анхаарлаа хандуулбал Талхиз жотын анхны хайгуулчид, аялагчид тус хотын нутаг дэвсгэр их байсныг илтгэдэг. Мөн энэ суурингийн нутаг дэвсгэрт багтсан боловч судлагдаагүй суурин газруудын тухай ярьж байна. Гэвч зуун тавин жил судлагдсан Талгар суурин түүхэн дурсгалт газрын хувьд онцгой ач холбогдолтой, байр суурь эзэлдэг нь дамжиггүй. Өнөөг хүртэл малтлагын явцад олдсон үнэт эд зүйлс тус улсын олон музей, музей нөөцөд хадгалагдаж байна. Олдворуудын дунд та импортын зүйлсийг харж болно. Энэ нь дундад зууны үеийн Талгар суурин нь олон улсын худалдаа сайн хөгжсөн гар урчууд, үнэт эдлэлийн холбоодын төв байсан болохыг харуулж байна. Их торгоны зам дагуу орших суурингийн хөгжилд гадаад харилцаа ямар их нөлөө үзүүлсэнийг харж болно. Талгар бол Жетысу дахь түүх, соёлын өвийн хамгийн чухал дурсгалуудын нэг юм. Гэсэн хэдий ч зарим суурин газарт судалгаа хийх шаардлагатай хэвээр байгааг үг нийтлэлд дурджээ. Түлхүүр үг. Талхиз, эртний суурин, худалдаа, судлаач, археологи, дундад зууны, олдвор, олон улсын, музей